The impacts of the external shocks between 2001-2003 on intergenerational mobility: An application of estimating permanent income with machine learning - Xu, Yangyuntao. (Tufts University. Tisch Library., 2019)
This paper finds that machine learning can overcome the life-cycle bias in the process of estimating permanent income, where the permanent income is defined as at least 5-years' average income between 30 and 40. In order to measure the impacts of external shocks, the Bush Tax cuts and economic recession, on intergenerational mobility, dividend income is chosen as identification strategy. This quasi-experiment shows that economic recession brought about a heterogeneous decrease in mobility by 35.7%, and the Bush Tax Cut at 2003 brought about a heterogeneous decrease in mobility by 16.9%. Though the effect of the tax cut is not significant, it might be caused by an inaccurate estimated error in the OLS regression. In addition, this paper finds that any instrumental variables used in the estimation are not supposed to be used in the second stage regression.; Thesis (M.S.)--Tufts University, 2019.; Submitted to the Dept. of Economics.; Advisor: Jeffrey Zabel.; Committee: Yannis Ioannides.; Keywords: Economics, and Labor economics.